Numerical simulation and field experiment study of the supersonic gas jet subsoiler based on DEM - Xia Li; Zhipeng Zhao; Birong You; Xuhui Wang; Tianyu Qi; Hang Zhu; Tao Qin (PLoS ONE, 2025)
To tackle the challenges of high draft resistance, limited subsoiling range, and ineffective subsoiling results in conventional subsoiling methods, this study combines the structure of an air cannon with that of a wing-type subsoiler to design a novel pneumatic blast subsoiling device. First, soil bin experiments were conducted to verify the feasibility of using the air cannon for pneumatic soil fracturing. A soil model was created in EDEM (Engineering Discrete Element Method)based on field conditions to analyze the subsoiler’s force distribution, ensuring the nozzle remains undeformed and the subsoiling process runs smoothly. Subsequent field experiments were conducted to evaluate the subsoiling effect under different working depths, speeds, and air pressures. The experimental results show that, compared with the conventional airfoil-shaped subsoiler, the supersonic gas jet subsoiler achieves optimal performance at a tillage speed of 0.5 m/s and a tillage depth of 380 mm. Under these conditions, the maximum drag reduction rate reaches 16.66%, and the soil disturbance area increases by up to 22.48%, significantly enhancing the drag reduction effect and soil fragmentation efficiency during subsoiling operations. Furthermore, the subsoiling effect was further improved as the working speed decreased and the frequency of air blasts increased, satisfying the subsoiling operation assessment standards. In conclusion, this study offers design insights for the development of innovative agricultural soil cultivation tools by identifying a more efficient new research approach in addition to conventional subsoiling techniques for lowering resistance and energy consumption.